P178 Role of prognostic nutritional index in predicting severity in active ulcerative colitis. (25th January 2019) - Giordano, A; Ribolsi, M; Balestrieri, P; Emerenziani, S; Cicala, M
Abstract: Background: A large proportion of patients with IBD shows an impairment of nutritional status. Prognostic nutritional index (PNI) has been described as predictor of colectomy and morbidity/mortality during surgery for ulcerative colitis (UC). The aim of the present study was to investigate the correlation between PNI and indices of severity in active UC and the association of PNI with the need for medical or surgical therapy. Methods: Consecutive UC patients, referring to our IBD unit, underwent full colonoscopy to assess Mayo endoscopic subscore (MES), Montreal classification (MC) and full Mayo score (FMS). Active patients were defined as FMS >2. Blood exams including C-reactive protein (CRP), serum albumin and complete blood count were analysed. PNI was calculated according to formula: 10 × serum albumin (g/dl) + 0.005 × total lymphocyte count. Patients with previous (last 3 months) use of steroids, immunosuppressants, biological therapy or surgery, use (last 2 weeks) of topical therapy, any ongoing infectious, oncological, metabolic disease in the last 6 months were excluded. Patients were followed up for 30 days and the possible initiation of steroids, biological and immunosuppressive therapy or colectomy was assessed. Ninety-five controls were enrolled among patients referring for IBS symptoms. Results: From 2016 to 2018, 95 active UC patients (47 females) were enrolled. UC patients displayed a median PNI (35.43, IQR 29.91–38.81) significantly lower than controls (40.62, IQR 38.11–41.51). Median PNI values discriminated patients according to disease severity (FMS mild 3−6: PNI 36.72, moderate 4–10: 35.67, severe >10: 29.48, p = 0.001; MES 1: PNI 39.12, 2: 36.44, 3: 31.74, p = 0.001; MC E1: PNI 37.81, E2: 36.21, E3: 32.77, p < 0.001). Multiple logistic regression analysis showed that lower PNI values were associated with the need for steroids/biological therapy within 30 days (OR 1.3), irrespective of age, sex, BMI, disease extent, clinical/endoscopic severity. According to ROC curves, a PNI cut-off (38.06) was identified to discriminate patients from controls (AUC 0.835, sensitivity 78%, specificity 28%) and divide patients into 2 groups. Conclusions: PNI appears to be a novel and promising biomarker associated with disease activity. Our findings show that PNI might be considered a reliable predictor of steroids or biological therapy in active UC.